2019
DOI: 10.1016/j.jhep.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

NK-cell responses are biased towards CD16-mediated effector functions in chronic hepatitis B virus infection

Abstract: Frequent HBV/HCMV co-infection is associated with the expansion of memory-like NK cells. Memory-like NK cells are largely conserved in chronic hepatitis B virus infection. Memory-like NK cells determine the NK-cell response in chronically hepatitis B virus-infected patients. Adaptive antibody-dependent NK-cell response is increased in chronic hepatitis B virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 46 publications
7
31
1
Order By: Relevance
“…Compared with conventional FcεRIγ+CD56 dim NK cells, this NK subpopulation displays different metabolic properties, including a higher fraction of functional, polarized mitochondria, and a stable epigenetic signature, along with increased CD16-mediated degranulation potential, which skews the whole NK cell population toward a higher CD16 sensitivity with enhanced ADCC. These data show the mutual influence of HBV- and HCMV-persisting infections on the NK cell repertoire, which significantly affects the immune response to chronic HBV infection, and point to the usefulness of HCMV co-infection evaluation in the application of immunotherapeutic approaches targeting NK cells for an HBV cure [49]. Moreover, KLRG1 upregulation has been detected on circulating and intrahepatic memory-like FcεRIγ-CD56 dim NK cells from CHB patients, which characterizes a subset with anti-fibrotic function exerted by a strong TRAIL-mediated induction of hepatic stellate cell (HSC) apoptosis.…”
Section: Nk Cells In Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with conventional FcεRIγ+CD56 dim NK cells, this NK subpopulation displays different metabolic properties, including a higher fraction of functional, polarized mitochondria, and a stable epigenetic signature, along with increased CD16-mediated degranulation potential, which skews the whole NK cell population toward a higher CD16 sensitivity with enhanced ADCC. These data show the mutual influence of HBV- and HCMV-persisting infections on the NK cell repertoire, which significantly affects the immune response to chronic HBV infection, and point to the usefulness of HCMV co-infection evaluation in the application of immunotherapeutic approaches targeting NK cells for an HBV cure [49]. Moreover, KLRG1 upregulation has been detected on circulating and intrahepatic memory-like FcεRIγ-CD56 dim NK cells from CHB patients, which characterizes a subset with anti-fibrotic function exerted by a strong TRAIL-mediated induction of hepatic stellate cell (HSC) apoptosis.…”
Section: Nk Cells In Hbv Infectionmentioning
confidence: 99%
“…Some conflicting results have been reported due to the wide spectrum of different clinical conditions characterizing the natural history of HBV infection [3]. As compared with healthy donors, a high expression of some activation/proliferation markers and death ligands (TRAIL) was observed both on peripheral and intrahepatic NK cells from chronic patients [47,48,49], particularly in the active hepatitis stage [50,51,52,53,54,55,56]. Intrahepatic NKG2D up-regulation was proposed to mediate NK activation and liver inflammation, which was particularly amplified in patients with acute-on-chronic liver failure (ACLF) [57].…”
Section: Nk Cells In Hbv Infectionmentioning
confidence: 99%
“…Similarly, a study showed that NK cells with a less mature phenotype, NKG2A + CD57 - NKG2C - (CD57 + is a marker of terminal differentiation), were associated with protection from leukemia relapse and improved OS [92]. This is also contrary to the conventional knowledge that mature and memory-like NKG2A − selfKIR + CD57 + NKG2C + NK cells generated by cytokine stimulation or CMV infection are more efficacious [93,94,95,96,97,98]. Although a unifying explanation for these seemingly contradictory findings is not yet available, recent observations suggest that the phenotype of NK cells determines the function, and CD56 bright or CD56 superbright NK cells may not only differentiate into mature cytotoxic NK cells, but also secrete enough cytokines to overcome the immunosuppressive tumor microenvironment [99].…”
Section: Strategies To Enhance the Effect Of Nk Cell Therapymentioning
confidence: 99%
“…[ 43 , 50 ] In short, NK cells display a functional dichotomy in CHB patients, characterized by impaired noncytolytic antiviral capacity such as IFN-γ production and enhanced or preserved cytotoxic function such as the degranulation capacity. [ 51 , 52 ] Furthermore, HIV-infected individuals exhibit significantly enhanced degranulation and IFN-γ production but no difference in IL-10 level compared with HCs. Our results are consistent with previous reports, [ 18 , 53 ] suggesting that NK cell functions are greatly enhanced in individuals with PHI relative to HCs.…”
Section: Discussionmentioning
confidence: 99%